Jesuit Rhetoric across Space and Time : Local and Global Perspectives - Awianowicz, Bartosz,; Brereton, John,; Conte, Sophie,; Gannett, Cinthia,; Kraus, Manfred,; Wright, Elizabethada, (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
A product of Renaissance educational thought, Jesuit rhetoric has trained generations of churchmen and lay citizens right up to the present day. This book aims to show the wealth of current international research on Jesuit rhetoric, in its pedagogical dimension (from sixteenth-century manuals to today's university writing courses), its practical implementation (in speeches, music or theology). These dialogues span both religious contexts-engagements with Protestants, Jews, Orthodox Christians, and Dominicans-and geographical ones, including encounters between Europe and regions such as Sri Lanka, China, and Japan.